2014
DOI: 10.1073/pnas.1411185111
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and minimal gene requirements for the alternative iron-only nitrogenase in Escherichia coli

Abstract: All diazotrophic organisms sequenced to date encode a molybdenum-dependent nitrogenase, but some also have alternative nitrogenases that are dependent on either vanadium (VFe) or iron only (FeFe) for activity. In Azotobacter vinelandii, expression of the three different types of nitrogenase is regulated in response to metal availability. The majority of genes required for nitrogen fixation in this organism are encoded in the nitrogen fixation (nif) gene clusters, whereas genes specific for vanadium-or irondepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 51 publications
4
81
0
Order By: Relevance
“…Although some of the underlying gene clusters have been studied in detail, the purpose of others, such as the anf operon, is still puzzling (Yang et al, 2014). On the other hand can some capabilities of bacteria not be explained by the presence or absence of genes per se .…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the underlying gene clusters have been studied in detail, the purpose of others, such as the anf operon, is still puzzling (Yang et al, 2014). On the other hand can some capabilities of bacteria not be explained by the presence or absence of genes per se .…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains used in this study are listed in Table S2. Media and antibiotics were used as described (28) and are detailed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The C 2 H 2 reduction method was used to assay nitrogenase activity as described (28). Details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on extensive early Mo and W model work, [3] Schrock [4] and Nishibayashi [5] have reported Mo-containing coordination complexes (A and B in Figure 1, respectively) that facilitate catalytic N 2 reduction to NH 3 in the presence of suitable acids and reductants. Because Fe is (i) the only transition metal known to be essential to enzymatic nitrogenase function, [6] and (ii) the predominant transition metal catalyst used in the Haber-Bosch ammonia synthesis, [7] studying N 2 reduction chemistry at well-defined Fe model complexes is of interest. [8,9] Recently, our lab demonstrated that Fe coordination complexes (C in Figure 1) are capable of modest catalytic N 2 reduction to NH 3 .…”
mentioning
confidence: 99%